2013
DOI: 10.2478/bvip-2013-0054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic methods to distinguish between calves persistently and transiently infected with bovine viral diarrhoea virus in respect to the presence of maternal antibodies

Abstract: Two issues concerning virus detection and identification of persistently infected (PI) cattle were analysed in the study: 1) interference by maternal antibodies and 2) discrimination between PI and transiently infected (TI) animals. Antigen ELISA and RT-PCR based methods were compared using serum samples from natural and experimental PI and TI calves. RT-PCR and realtime RT-PCR using primers within 5'UTR region were more sensitive in detecting PI animals than E rns and NS3 antigen capture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Although there is information in the literature regarding the implementation of RT-qPCR Cq cutoff points for some diseases of importance in human and veterinary medicine, mainly in the former (8,10,27,28), there are no studies establishing viral load cutoff points to causally associate RVA infection with disease in diarrheic calves.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is information in the literature regarding the implementation of RT-qPCR Cq cutoff points for some diseases of importance in human and veterinary medicine, mainly in the former (8,10,27,28), there are no studies establishing viral load cutoff points to causally associate RVA infection with disease in diarrheic calves.…”
Section: Discussionmentioning
confidence: 99%
“…The method used by some authors is considered more accurate by the identification of viral RNA. In a study carried out in Poland comparing the ELISA-Ag based on the Erns protein -a structural protein -, the Realtime RT-PCR (qRT-PCR), and the ELISA-Ag test based on the NS3 protein -a non-structural protein -it was observed that it was possible to identify PI animals in 89.7%, 100% and 3.4% of cases, respectively (Larska et al 2013). Similarly, a previous study has described the superiority of RNA detection regarding ELISA on the presence of maternal antibodies (Zimmer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the positive results from the BVDV antibody ELISA tests, serial dilutions (from 1:5 to 1:320) of seven randomly selected serum samples from buffalo and nine cattle sample with doubtful result in ELISA-1 and ELISA-4 were tested with VNT as described previously (Larska et al 2013). The Singer strain of CP BVDV-1a was used to determine neutralizing antibody titers in BT (bovine turbinate) cells.…”
Section: Virus Neutralization Test (Vnt)mentioning
confidence: 99%